Temperament and character in men with autism spectrum disorder: A reanalysis of scores on the Temperament and Character Inventory by individual case matching - Vuijk, Richard (Contemp Clin Trials Commun, 2018)
BACKGROUND: Interest in autism spectrum disorders (ASD) in adulthood is increasing. Although a person may be diagnosed with ASD, the diagnosis reveals little about the individual's temperament, character, and personality. Also, relatively little is known about the personality of adults with ASD. METHOD: A reanalysis of scores on the Temperament and Character Inventory (TCI) administered to a group of 66 normally intelligent men aged 18–63 years, diagnosed with ASD, by individual case matching to a comparison group of 66 men from the general population drawn from the TCI manual. RESULTS: Compared to the comparison group, men with ASD scored significantly higher on the scale for Harm Avoidance, and lower on Novelty Seeking, Reward Dependence, Self-Directedness, and Cooperativeness. CONCLUSIONS: In this study the score pattern for temperament and character found in men with ASD by individual case matching confirms and strengthens earlier general group matching findings emerging from our 2012 study and from studies from Sweden and the Netherlands.